A beekeeper’s kit of the First Byzantine period in Eleutherna (Crete) - Yangaki, Anastasia G. (Journal of Greek Archaeology, 2022)
The site of ancient Eleutherna is located in the regional unit of Rethymnon, around 25 km away from the town of that name, in the region of Mylopotamos, northwest of Mount Ida. Hills characterise the archaeological zone of the site, deeply cut through by two streams, to the east and to the west. It is a naturally fortified site, blessed with rich vegetation. Systematic excavations in Eleutherna by the University of Crete began in 1985. The whole site was divided into three Sectors. The eastern and western sides of one of these hills, Pyrgi, have been excavated (Sectors I and III, respectively), as well as the hill of Pyrgi (Figure 1), itself, which corresponds to the acropolis, and the hill to west of Pyrgi, Nisi (Sector II). These two hills are oriented north-south. The former has a more pointed shape at the northern end, and consists of terraces that have an elevation of 320 to 380 m. There lies the Central Plateau of the Acropolis of Eleutherna. Thanks to the investigations, architectural remains from various eras have been revealed on the eastern and western sides, as well as on the end of each of these hills. During the period from the 4th until at least the first half of the 8th century AD, forming part of the so-called First Byzantine period of the island, which is of interest to us, Eleutherna experienced great growth. Important architectural remains from a settlement of that period are mainly concentrated in the valley east of Pyrgi (Sector I) and on the hill of Pyrgi (Sector II).